PKS 2250–351: A giant radio galaxy in Abell 3936. (2020) - Seymour, N.; Huynh, M.; Shabala, S. S.; Rogers, J.; Davies, L. J. M.; Turner, R. J.; O'Brien, A.; Ishwara-Chandra, C. H.; Thorne, J. E.; Galvin, T. J.; Jarrett, T.; Andernach, H.; et al.
Abstract: We present a detailed analysis of the radio galaxy PKS $2250{-}351$, a giant of 1.2 Mpc projected size, its host galaxy, and its environment. We use radio data from the Murchison Widefield Array, the upgraded Giant Metre-wavelength Radio Telescope, the Australian Square Kilometre Array Pathfinder, and the Australia Telescope Compact Array to model the jet power and age. Optical and IR data come from the Galaxy And Mass Assembly (GAMA) survey and provide information on the host galaxy and environment. GAMA spectroscopy confirms that PKS $2250{-}351$ lies at $z=0.2115$ in the irregular, and likely unrelaxed, cluster Abell 3936. We find its host is a massive, 'red and dead' elliptical galaxy with negligible star formation but with a highly obscured active galactic nucleus dominating the mid-IR emission. Assuming it lies on the local M – $σ$ relation, it has an Eddington accretion rate of $λ_{\rm EDD}\sim 0.014$ . We find that the lobe-derived jet power (a time-averaged measure) is an order of magnitude greater than the hotspot-derived jet power (an instantaneous measure). We propose that over the lifetime of the observed radio emission ( ${\sim} 300\, $ Myr), the accretion has switched from an inefficient advection-dominated mode to a thin disc efficient mode, consistent with the decrease in jet power. We also suggest that the asymmetric radio morphology is due to its environment, with the host of PKS $2250{-}351$ lying to the west of the densest concentration of galaxies in Abell 3936.